5x-13=47

Simple and best practice solution for 5x-13=47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-13=47 equation:


Simplifying
5x + -13 = 47

Reorder the terms:
-13 + 5x = 47

Solving
-13 + 5x = 47

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 5x = 47 + 13

Combine like terms: -13 + 13 = 0
0 + 5x = 47 + 13
5x = 47 + 13

Combine like terms: 47 + 13 = 60
5x = 60

Divide each side by '5'.
x = 12

Simplifying
x = 12

See similar equations:

| 4x+8=98-6x | | 5x-13=35 | | 2x+19=12x-91 | | 6X+10=-22-10X | | 105-3x=4x+21 | | 148-3X=6X+13 | | 9x-22=3x+2 | | 2x+7=4x-1 | | -38-4x=12-9x | | 8(x-2)+18(1-x)=-6 | | 101-5x=9x+17 | | 3(x-4)+2(2x+3)=15 | | 83-6X=7X+18 | | 3x+5=68-4x | | 2x+31=11x-77 | | 2x+31=11x-7 | | 3(x-4)+2(x+2)=4 | | 6x+3=9x-3 | | 6x+66=12x+12 | | 4x+y=28 | | 242.36=29.2(5p-5) | | 10x-14=6x+2 | | p+p+32+4p-39=589 | | 5.4=a-(-1.8) | | -18+h=28 | | g+(-5)=27 | | x+47=-23 | | 15x=165 | | 1x+18+5x=0 | | X+12=22 | | 6x-3=589 | | 8n=288 |

Equations solver categories